Identification of Families with Stunting in the Working Area of the Astambul Martapura Community Health Center, Banjar Regency - fauziah, erna fauziah; Mariana, Evi Risa; Pratiwi, Niken; Hutagaol, Ruthmauli; Nurhadijah, Sitti; Fratama, Ferry Fadli (Poltekkes Kemenkes Banjarmasin, 2024)
Stunting is a chronic nutritional problem and is an important problem in Indonesia. The emergence of the problem of stunting can have a fatal impact on children if it is not addressed. One of the main causes of stunting is a lack of nutritional intake in the first 1000 days of life or a lack of nutritional intake for a long time. This causes children to experience growth disorders, namely height that is not appropriate for their age, decreased productivity, health problems, and ultimately can cause generation loss in Indonesia. The impact of stunting is metabolic disorders in the body. The research results show that from the results of the questionnaire, it was found that the risk factors that cause stunting in families with stunting are: Nutritional Status, and the results of the questionnaire conducted using in-depth interviews show that visits to Posyandu are not routinely attended every month, the processing and presentation of children's food is less varied. , low in protein and low in nutritional value.